DISTRIBUTION ANALYSIS OF ENLARGED CELLS DERIVED FROM GROUPER SLEEPY DISEASE IRIDOVIRUS (GSDIV) INFECTED HUMPBACK GROUPER Cromileptes altivelis - Indah Mastuti; Ketut Mahardika (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Characteristic of Megalocytivirus infection has been known to produce formation of inclusion body bearing cells (IBCs) on internals organs of fish predominantly on spleen and kidney. Megalocytivirus that infected grouper is known as Grouper Sleepy Disease Iridovirus (GSDIV). This study was conducted to answer the effect of entry sites of GSDIV on distribution of enlarged cells formed on the internal organs of humpback grouper Cromileptes altivelis. Enlarged cells were observed histologically under the light microscope on spleen, head kidney, trunk kidney, liver, gill, heart, stomach, intestine, muscle and brain. Entry sites were designated to intramuscularly injection, intraperitoneally injection, dipped gill and inoculum added feed. Enlarged cells were formed on spleen, head kidney, trunk kidney, liver, gill, heart, stomach, muscle, except on intestine and brain. All the entry sites resulted in formation of enlarged cells on spleen, head kidney, trunk kidney, liver, heart. Spleen and head kidney were the most frequent observed organ. These results suggested that distribution of enlarged cells were not affected by the entry site of GSDIV.